Vegetarian diet - how does it affect our body? - Natalia Tekiela; Natalie Papachristoforu; Daria Michałka; Zuzanna Gałuszka; Monika Makar; Tomasz Bartuś; Emilia Bąk; Justyna Głowacka; Aleksandra Kocjan; Radosław Chmiel (Quality in Sport, 2025)
Introduction and Purpose of Research: